PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PEMBERIAN TUGAS PADA SISWA DI MIN 1 TABALONG - Muhammad Husni (Cross-border, 2021)
One way to increase students' learning motivation in Islamic religious education subjects is through giving assignments to students. Based on this statement, this research can be focused on increasing motivation to learn Islamic religious education through giving assignments to students at MIN 1 Tabalong. The subjects in this study were two PAI teachers and several students at MIN 1 Tabalong. While the object of this research is to increase the motivation to learn Islamic religious education through giving assignments to students at MIN 1 Tabalong. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique uses qualitative and provides conclusions using general methods based on data in the field. The results of this study indicate that increasing motivation to learn Islamic religious education through giving assignments to students at MIN 1 Tabalong is illustrated by 1) PAI teachers have given assignments to their students and the assignments have been adjusted to the Learning Implementation Plan (RPP). 2) The assignments given by PAI teachers are very numerous and this has made students unable to do them, so that these tasks are assisted by students' parents in doing them. 3) The tasks given by the PAI teacher to their students are quite clear, because students can understand the tasks that have been given by the PAI teacher, both the type of task and the time in completing these tasks.